Pengaruh Pola Asuh Orangtua terhadap Perkembangan Sosial pada Masa Remaja di SMP Negeri 17 Kota Jambi - Rugayah Rugayah; Nelyahardi Gutji; Hera Wahyuni (Journal on Education, 2023)
This study is based on the difference in child development of children based on parenting patterns. The purpose of this study is to reveal the level of parenting, and reveal the level of social development of teenagers in SMP Negeri 17 Jambi city and revealed the influence of parenting pattern of social development in adolescence. In this study are limited to 1) the level of social development in teenagers 2) students who have parents (father and mother) work 3) research subjects to students of class VIII SMP Negeri 17 Jambi city. Social development is the achievement of maturity in social relationships. While the parent's pattern works is a parent way in guiding, treating and educating children despite the occupational work. How parents are parenting without leaving her job. This type of research is quantitative with expost facto method. Data collection techniques are using questionnaire and sampling technique using total sampling with sample amount of 80 students. Based on the results of the study showed that there was a significant influence between variables X and variable Y. The influence was evidenced by the value of the sig. 0.05 which shows there is an influence between variables. At the same time, the value of the counter is 0,170 which is interpreted quite strongly. Therefore cooperation between teachers and parents will be well in order to be able to equalize and guide the direction of child's social development.